6
$\begingroup$

Let $\sigma,\tau \in S_n$. Prove that $\sigma \tau$ and $\tau \sigma $ have the same cycle type.

I was thinking that you could rewrite $\sigma=g_1\cdots g_k$ with $g_i$ disjoint cycles and $\tau=h_1\cdots h_l$ with $h_i$ disjoint cycles. But I don't know what to do next, as $g_i$ and $h_j$ doesn't have to be disjoint.

Edit: Could I prove it like this ?

We can write $σ$ in disjoint cycles: $σ=σ_1...σ_r$ with lenghts $l_1,...l_r$. So you get: $σ_1=(a_1...a_{l_1}), σ_2=(b_1...b_{l_2}), σ_3=...$.

Which gives: \begin{align*} τστ^{-1}&=τσ_1...σ_rτ^{-1}\\ &=τσ_1(τ^{-1}τ)σ_2(τ^{-1}τ)...(τ^{-1}τ)σ_rτ^{-1}\\ &=τ(a_1...a_{l_1})τ^{-1}τ(b_1...b_{l_2})τ^{-1}τ...τσ_rτ^{-1}\\ &=(τ(a_1)...τ(a_{l_1}))(τ(b_1)...τ(b_{l_2}))...τσ_rτ^{-1}\\ \end{align*}

Therefore $σ$ and $τστ^{-1}$ have the same cycle type. So $τσ$ and $στ$ have the same cycle type.

$\endgroup$
6
$\begingroup$

Hint: they are conjugate elements of the group.

$\endgroup$
  • 5
    $\begingroup$ My book introduces conjugates in the next chapter. $\endgroup$ – 90intuition Mar 19 '13 at 15:59
5
$\begingroup$

First consider the case that $\tau$ is a single cycle, say $\tau = (i_1,i_2,\ldots,i_k)$. You should be able to compute $\sigma\tau$ and $\tau\sigma$ explicitly in this case. Then figure out how to generalize when $\tau$ is a product of disjoint cycles: for this try inserting copies of $\sigma^{-1}\sigma$ in various places of the product $\sigma\tau\sigma^{-1}$ when $\tau$ is written as a product of disjoint cycles.

$\endgroup$
  • $\begingroup$ This one did it ! Thanks $\endgroup$ – 90intuition Mar 19 '13 at 20:09
  • 1
    $\begingroup$ Let $σ=σ_1...σ_r$ with $σ_1=(a_1...a_{l_1}), σ_2=(b_1...b_{l_2}), σ_3=...$. Then you get: \begin{align*} τστ^{-1}&=τσ_1...σ_rτ^{-1}\\ &=τσ_1(τ^{-1}τ)σ_2(τ^{-1}τ)...(τ^{-1}τ)σ_rτ^{-1}\\ &=τ(a_1...a_{l_1})τ^{-1}τ(b_1...b_{l_2})τ^{-1}τ...τσ_rτ^{-1}\\ &=(τ(a_1)...τ(a_{l_1}))(τ(b_1)...τ(b_{l_2}))...τσ_rτ^{-1}\\ \end{align*} $\endgroup$ – 90intuition Mar 19 '13 at 20:38
  • $\begingroup$ I hope that this is what you meant. $\endgroup$ – 90intuition Mar 19 '13 at 20:38
  • $\begingroup$ Since this answer worked for you, @90intuition, please accept it by clicking the checkmark :) $\endgroup$ – Shaun Dec 24 '18 at 21:11
5
$\begingroup$

First, it suffices to prove that $\tau\sigma\tau^{-1}$ and $\sigma$ have the same cycle type.

Suppse one of the cycles in $\sigma$ is $(a_1,a_2,\dots,a_n)$. Then, try to prove that there is a corresponding cycle in $\tau\sigma\tau^{-1}$ that is $\big(\tau(a_1),\tau(a_2),\dots,\tau(a_n) \big)$.

If $\sigma$ sends $a_1$ to $a_2$, what does $\tau\sigma\tau^{-1}$ send $\tau(a_1)$ to?

$\endgroup$
  • $\begingroup$ Specifically, it suffices to show $\alpha\beta\alpha^{-1}$ and $\beta$ have the same cycle type, because then one can set $\beta=\tau\sigma$ and $\alpha=\sigma^{-1}$ to conclude $\sigma\tau$ and $\tau\sigma$ have the same cycle type. Which is also the hint of Robert's answer. (Sorry for the anachronistic comment.) $\endgroup$ – whacka Aug 2 '15 at 21:06
3
$\begingroup$

In the light of @Robert's answer, if $x$ and $y$ are two permutations of a set $\Omega$, and $x=(\xi_1,\xi_2,...,\xi_k)$ then $$y^{-1}xy=(\xi_1^y,\xi_2^y,...,\xi_k^y)$$ In fact, in the product $xy$ we expect to have the result of first applying the mapping $x$ and then the mapping $y$. This is what @Robert's trying to tell you.

$\endgroup$
  • $\begingroup$ Nice! $\quad \ddot \smile \quad +1 \quad$ $\endgroup$ – Namaste Mar 20 '13 at 0:15
0
$\begingroup$

Suppose that $\sigma \tau=(a_1a_2\cdots a_k)(b_1b_2\cdots b_{\lambda})\cdots$.
Then $\tau\sigma(\tau(a_i))=\tau(\sigma\tau(a_i))=\tau(a_{i+1})\ldots$

Show that $\tau\sigma=\left(\tau(a_1)\tau(a_2)\cdots\tau(a_k)\right)\left(\tau(b_1)\tau(b_2)\cdots\tau(b_{\lambda})\right)\cdots$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.